Investigation of Serratia marcescens surgical site infection outbreak associated with peroperative ultrasonography probe. (May 2021) - Géry, A.; Mouet, A.; Gravey, F.; Fines-Guyon, M.; Guerin, F.; Ethuin, F.; Borgey, F.; Lubrano, J.; Le Hello, S.
Summary: Early postoperative infections due to Serratia marcescens have been reported by both clinicians and microbiologists in our teaching hospital. Here, we present an interlinked clinical, epidemiological, environmental and genomic investigation of this outbreak due to a T-shaped intraoperative probe contaminated by S. marcescens used during peroperative ultrasonography in laparoscopic liver resection.